Histological and transcriptome analysis uncover a robust early PTI and ETI-associated immune response in Musa acuminata subsp. burmannica accession ‘Calcutta 4’ to Fusarium oxysporum f. sp. cubense Subtropical Race 4 - Costa, Érica de Castro; Bastos, Lucas Santos; Ramos, Andresa Priscila de Souza; Rocha, Leandro de Souza; Amorim, Edson Perito; Ferreira, Claudia Fortes; Serão, Nicola Vergara Lopes; Togawa, Roberto Coiti; Grynberg, Priscila; Miller, Robert Neil Gerard (Frontiers in Plant Science, 2025)
IntroductionBanana (Musa spp.) is a globally significant crop and a staple food in the diet of millions of people. However, commercial cultivars are highly susceptible to Fusarium wilt, a devastating disease caused by Fusarium oxysporum f. sp. cubense (Foc). Tropical race 4 (TR4) and Subtropical race 4 (STR4) pose significant threats to banana production, including ‘Cavendish’ (AAA group), with STR4 pathogenic only in subtropical regions. Genetic resistance is the most effective strategy to combat Foc, underscoring the importance of advancing understanding of resistance mechanisms.MethodsHere, we identified and validated genes involved in the resistance response to Foc STR4 through RNA-seq and RT-qPCR analyses. Two genotypes were evaluated: ‘Calcutta 4’ (a resistant wild genotype, AA) and ‘Prata-Anã’ (a susceptible commercial genotype, AAB). Seedlings of ‘Calcutta 4’ and ‘Prata-Anã’ were inoculated with Foc STR4 isolate 218A, and root samples from ‘Calcutta 4’ were collected at 1, 2, and 4 days after inoculation (DAI) for RNA-seq analysis.ResultsComparative histological studies between the genotypes revealed defence responses, such as callose deposition and phenolic compound production, occurring exclusively in ‘Calcutta 4’ at 1 and 2 DAI, while colonization by Foc STR4 was observed only in ‘Prata-Anã’ at 8 and 15 DAI. RNA-seq analysis identified 1416 differentially expressed genes (DEGs) in ‘Calcutta 4’, based on comparisons between inoculated and non-inoculated control plants, log2FC >2 and <-2, and adjusted p-value for FDR at <0.05, with a rapid upregulation of 752 DEGs at 2 DAI, including genes associated with pattern recognition receptors, chitinases, phytohormones, resistance genes (from the NLR family), TFs, and systemic acquired resistance. Functional pathway analysis highlighted coordinated defence responses in ‘Calcutta 4’ to Foc STR4.DiscussionTogether with functional validation of selected genes via RT-qPCR, these findings provide a foundation for the application of candidate genes in genetic improvement via introgression or gene-editing approaches. Given the close phylogenetic relationship between Foc STR4 and TR4, introgression of defense-related genes also holds promise for developing varieties that are resistant to both race 4 pathogens, relevant for mitigating the global impact of Fusarium wilt epidemics on banana production.